Paradoxes of Reactance During the COVID-19 Pandemic: A Social-psychological Perspective - V., Katharina; Häfner, Michael (Javnost-The Public, 2021)
This study aims to explain the dynamics of compliance towards the measures to contain the coronavirus in 2020 by drawing on the theory of psychological reactance. We discuss our findings in a model that distinguishes between catalysts and buffers of reactance arousal on an individual level and hypothesises how these may lead to compliant or resistant behaviour as acts of resilience in the public sphere. In an online survey (N = 766, May 2020, Germany), we found that reactance arousal towards the restrictions to contain the coronavirus depended on the individual assessment of the limitations of freedom. Data suggest that health related fear buffers reactance arousal, whereas surprisingly, sorrow and cognitive dissonance amplify it. Anger and a critical political attitude towards the government correlate positively with the mobilising power of reactance. We argue that these are essential elements that push individual reactance arousal over the threshold into the public sphere, where it serves to shove resilience towards resistance. Our study expands this essential social-psychological theory to be a driver not only in the individual but also in public behaviour, opening a new perspective on the tipping point between resilience and resistance in the public sphere during this crisis and beyond.